Analysis of Covid-19's impacts on the brazilian real estate market (Research, Society and Development, 2020)
The Brazilian real estate market has been experiencing a growth process for the past five years. In this perspective, this article has as its main objective to verify of the likely impacts on the sector due to the current pandemic of Covid-19, as well to present of the current national panorama of the real estate market. As secondary objectives, evaluate the sector's behavior in each region of Brazil and the correlation between the studied indexes. The study was carried out based on analysis of official sector indicators, by verifying their behavior in the period between 2016 and 2020, with the aid of descriptive statistics. The results showed evidence of impact due to the pandemic in the 2nd quarter of 2020, with a reduction in launches and sales of residential properties, an increase in the average rental price index, and a reduction in the IPCA. In the 1st quarter of 2020, there were no significant impacts due to the pandemic; the launch and sales indicators registered a peak with higher numbers. From the analyzes carried out, it can be said that the evolution curve of the real estate market has strong characteristics with the evolution of the sector in the Southeast region, which was the most heated in the last five years. The existence of annual cycles by quarters in launches and sales was also evidenced. The topic addressed is relevant for presenting reliable and truthful information to society and investors, as well as to all those interested in the sector.